2010
DOI: 10.4049/jimmunol.1001802
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ablation of Langerhans Cells Enhances Skin Immune Responses

Abstract: Understanding the function of Langerhans cells (LCs) in vivo has been complicated by conflicting results from LC-deficient mice. Human Langerin-DTA mice constitutively lack LCs and develop exaggerated contact hypersensitivity (CHS) responses. Murine Langerin-diptheria toxin receptor (DTR) mice allow for the inducible elimination of LCs and Langerin+ dermal dendritic cells (dDCs) after administration of diphtheria toxin, which results in reduced CHS. When Langerin+ dDCs have partially repopulated the skin but L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 30 publications
7
105
1
2
Order By: Relevance
“…The reason for this augmented reactivity is unclear, but it may be due to failing peripheral tolerance mechanisms in the absence of LC throughout life (1,11,32). More recently, aggravated CHS was also reported following acute LC ablation (33). How to reconcile the incongruent results obtained with the different inducible LCdepletion models remains elusive.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…The reason for this augmented reactivity is unclear, but it may be due to failing peripheral tolerance mechanisms in the absence of LC throughout life (1,11,32). More recently, aggravated CHS was also reported following acute LC ablation (33). How to reconcile the incongruent results obtained with the different inducible LCdepletion models remains elusive.…”
mentioning
confidence: 51%
“…The reason for enhanced reactivity observed thus far only in human Langerin bacterial artificial chromosome transgenic mice with constitutive or acute ablation of LC remains enigmatic (31,33), in particular, because CHS responses were unaffected in Batf3-deficient mice specifically lacking Langerin + CD103 + dermal DC (15). In these mice, CHS should have been attenuated if LC had a regulatory function, as has been suggested (31,33). In a mouse model independent of diphtheria toxin-mediated cell ablation, we demonstrated that CHS responses are reduced (and not enhanced) in the selective absence of LC (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As we have seen with other huLangerin transgenic mice, transgene expression was specific for LCs (13,16,17). In the dermis of YFP mice, only migratory LCs as defined by expression of muLangerin in the absence of CD103 expressed huLangerin (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…4). In unmanipulated mice in which the ratio of mLCs to m-DDCs in cLN is 1:3 rather than 1:1, the effect of LCs would be smaller, which may explain the lack of effect in some (9,33,34), but not all (7,8,35), models of contact sensitivity. The ability of LCs to suppress the response to antigen presentation by other DC subsets argues against the possibility that tolerance in our models is a default response to presentation of free antigen without active involvement of migrated skin DCs.…”
Section: Discussionmentioning
confidence: 99%